2000
DOI: 10.1159/000018475
|View full text |Cite
|
Sign up to set email alerts
|

Blastoid NK Cell Leukemia/Lymphoma with Cutaneous Involvement

Abstract: Malignant neoplasms from natural killer (NK) cells are characterized by their positivity for CD56 and absence of monoclonal TCR gene rearrangement. Recently, they have been classified into four main types (nasal and nasal-type NK cell lymphoma, aggressive NK cell leukemia/lymphoma, and blastoid NK cell leukemia/lymphoma), based on clinical features, racial predisposition, presence of azurophilic granules, immunophenotype and association with Epstein-Barr virus (EBV) infection. A 72-year-old Caucasian man prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The blastic natural killer cell lymphoma has emerged as a distinctive form of hematologic malignancy that has been renamed as hematodermic neoplasm, recognizing that the cell of origin is a plasmacytoid dendritic cell. [38][39][40][41][42][43] Like T-PLL, these tumors are aggressive neoplasms with a propensity to involve the skin and bone marrow early in its course and affect elderly individuals. The tumor cells express CD4, CD56, and CD123 and do not express CD2 or CD3.…”
Section: Discussionmentioning
confidence: 99%
“…The blastic natural killer cell lymphoma has emerged as a distinctive form of hematologic malignancy that has been renamed as hematodermic neoplasm, recognizing that the cell of origin is a plasmacytoid dendritic cell. [38][39][40][41][42][43] Like T-PLL, these tumors are aggressive neoplasms with a propensity to involve the skin and bone marrow early in its course and affect elderly individuals. The tumor cells express CD4, CD56, and CD123 and do not express CD2 or CD3.…”
Section: Discussionmentioning
confidence: 99%
“…Only two authors reported sustained CR (7%) after this therapy; one young patient with skin-restricted disease had radiotherapy; another, a 72-year-old man with widespread disease, was treated with cyclophosphamide, methotrexate, vincristine and intrathecal prophylaxis. 24,31 However, the observation time for the two patients was only 14 and 18 months, respectively. The median overall survival for all evaluable patients is only 9 months and Kaplan-Meier curves do not suggest curative potential for this therapeutic approach (Figure 2).…”
Section: Treatment Outcomementioning
confidence: 99%
“…This finding may be bolstered by the presence of megaloblastoid erythroid maturation and tumorassociated monocytosis. Fulminant leukemia is a common feature of HDT progression or relapse and is nearly always Chan et al, 8 DiGiuseppe et al, 9 Bayerl et al, 10 and Falcao et al 11 (Lympho)blastoid NK-leukemia/lymphoma Estalilla et al, 12 Ginarte et al, 13 present in the terminal stage. As described later, relapse as myelomonocytic leukemia also occurs.…”
Section: Clinical Featuresmentioning
confidence: 99%